Comparative Analysis of Measurement Precision in CBT and PBT using IRT among Undergraduates in Kwara State - SULYMAN, Rasaq (Ilorin Journal of Education, 2025)
The adoption of Computer-Based Testing (CBT) as an alternative to the traditional Paper-Based Testing (PBT) in response to demands for more efficient and proficient assessment methods in Nigerian universities has increasingly gained momentum across the country. This study presents a comparative analysis of Computer-Based Testing (CBT) and Paper-Based Testing (PBT) using Item Response Theory (IRT) among undergraduates in Kwara State University. The aim was to examine the psychometric properties of test items under both testing modes and determine their effectiveness in assessing students’ abilities. A total of 240 students were selected from two faculties and four departments across the two universities, with 30 respondents drawn from each department. A 10-item multiple-choice test was administered in both CBT and PBT formats. The results indicated that CBT yielded higher test information values, suggesting greater measurement precision compared to PBT. More so, CBT-based assessments showed better ability estimation (θ), demonstrate their capacity to more accurately measure student performance across ability levels. These findings highlight the psychometric advantages of CBT over PBT. It was recommended that higher institutions should invest in infrastructure and capacity-building for CBT implementation while ensuring inclusive access. The study supports the integration of IRT in educational assessment to enhance validity and reliability.